PENGARUH BEBAN KERJA TERHADAP KINERJA PEGAWAI DENGAN STRES KERJA SEBAGAI VARIABEL MEDIASI (Survei Pada Pegawai BPJS Kesehatan Cabang Surakarta) - Yuni Fakhtul Alifah; Lamidi Lamidi; Sunarso Sunarso (Universitas Slamet Riyadi, 2020)
The progress of an organization can not be separated contained in it. Human resources are the most important factor in carrying out all its activities in achieving a goal that is in the organization. The Health Social Security Organizing Agency (BPJS Kesehatan) is a Public Legal Entity responsible directly to the President who specifically provides the Indonesian public health insurance program. The objectives of this study are: 1) to analyze the significance of the effect of workload on work stress on Surakarta Branch BPJS employees. 2) to analyze the significance of the effect of workload on employee performance at BPJS Health Surakarta Branch. 3) to analyze the significance of the effect of work stress on employee performance in BPJS Surakarta Branch Health. 4) ) to analyze work stress in mediating workload on employee performance at BPJS Surakarta Branch Health. This research is a census research on Surakarta Branch BPJS Health employees. This type of data uses qualitative and quantitative data. Data sources use primary and secondary data. The population in this study were 89 employees of BPJS Health Surakarta Branch. The study sample was 89 people. Data collection techniques using questionnaires, observation and documentation. The classic assumption test uses tests; multicollinearity, heteroscedasticity, autocorrelation and normality. Data analysis techniques used multiple linear regression analysis, descriptive analysis, t test, F test, coefficient of detremination test and sobel test. The results showed that workload had a positive and significant effect on work stress, workload had a negative and not significant effect on employee performance, work stress had a negative and significant effect on employee performance, work stress mediated workload oon employee performance.